Perancangan Dan Pengembangan Website Profile Sekolah Charitas Batam - Herman; Anthony (Telcomatics, 2024)
Advancement in technology and communication can help reaching a larger audience easier and more efficient. Charitas Batam School, as an educational institution, has been using banners and brochures as tools to provide information to prospective parents of students. However, there are limitations in reaching a wider audience, especially in the current digital age. Therefore, schools and other organizations must have a profile website that showcases their activities, programs, and achievements. Hence, the author is engaged in community service by designing and implementing a profile website for Charitas School Batam. The method used for this project involves data collection through interviews and implementation using the SCRUM framework to ensure a smooth development process. The result is a profile website that has been successfully hosted and well-received by the school.